New camera trap data of the Pallas' cat Otocolobus manul (Pallas, 1776) from the Katon-Karagai National Park (Eastern Kazakhstan) - Gabdullina, Aliya U.; Amanbaev, Zhomart B.; Chelysheva, Renata A. (Altai State University, 2024)
The article presents new information on the location of the Pallas's cat in the territory of the Katon-Karagai National Park, including data obtained from camera traps.